2020
DOI: 10.3390/ijerph17093242
|View full text |Cite
|
Sign up to set email alerts
|

Individual Fit Testing of Hearing-Protection Devices Based on Microphones in Real Ears among Workers in Industries with High-Noise-Level Manufacturing

Abstract: Hearing-protection devices (HPDs) are particularly important in protecting the hearing of workers. The aim of this study was to prevent hearing damage in workplaces in Taiwan. It was conducted to determine the actual sound attenuation of the personal attenuation rating (PAR) values when wearing HPDs via measurements from field microphones in workers’ real ears (F-MIRE). Across 105 measurement trials for the Classic™ roll-down foam earplug HPDs worn by the workers, there were 23 cases of ineffective protection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Both the generalized linear model and logistic regression model showed that earplug attenuation had no significant effect on the hearing of participants. These findings are in agreement with the evidence from previous studies that the use of HPDs in the workplace is often inconsistent and not fully effective [ 7 , 9 , 18 , 19 , 20 , 21 , 22 ]. Specifically, these findings are consistent with Groenewold’s [ 5 ] report which showed self-reported use of hearing protection devices at work was not significantly associated with the odds of high-frequency threshold shifts among 19,911 noise-exposed U.S. workers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Both the generalized linear model and logistic regression model showed that earplug attenuation had no significant effect on the hearing of participants. These findings are in agreement with the evidence from previous studies that the use of HPDs in the workplace is often inconsistent and not fully effective [ 7 , 9 , 18 , 19 , 20 , 21 , 22 ]. Specifically, these findings are consistent with Groenewold’s [ 5 ] report which showed self-reported use of hearing protection devices at work was not significantly associated with the odds of high-frequency threshold shifts among 19,911 noise-exposed U.S. workers.…”
Section: Discussionsupporting
confidence: 93%
“…However, multiple studies of the training methods have shown that they failed to teach how to properly fit their earplugs [ 9 , 19 , 20 , 21 ]. Individual training along with HPD fit testing has been shown to teach poorly performing subjects to insert earplugs properly and achieve sufficient attenuation [ 7 , 9 , 21 , 22 ]. To improve earplug fitting skill and to train workers to wear them correctly, individual fit-testing was recommended to the surveyed auto parts factory.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, workers from the training group were shown how to wear plugs correctly. This training strategy has been adopted in numerous studies 10,21,23,24 and PARs improved significantly across these studies. Federman and Duhon 32 evaluated three different training paradigms with 79 US Marine Corps training recruits.…”
Section: Discussionmentioning
confidence: 99%
“…A number of fit‐test systems are commercially available, including 3M™ E‐A‐Rfit™ Dual‐Ear Validation System, VeriPRO fit‐test system, and the FitCheck Solo™ fit test system 15,20,21 . The 3M™ E‐A‐Rfit™ Dual‐Ear Validation System was introduced to Chinese HPD users several years ago and demonstrated value for verifying sufficiency of attenuation 22–24 .…”
Section: Introductionmentioning
confidence: 99%
“…Workplaces with a strong safety culture and that provide practical health and safety management are associated with greater adherence to wearing HPDs. There is a positive association between HPD use, training, years of service, education levels, gender, and type of HPD (Thepaksorn et al, 2018;Chien-Chen and Terng-Jou, 2020).…”
Section: Introductionmentioning
confidence: 99%